Interference-Contrast and Phase-Contrast Microscopy of Sporulation in Clostridium thermosaccharolyticum Grown Under Strict Anaerobiosis - Eller, Charles (1972)
Cells of Clostridium thermosaccharolyticum grown under strict anaerobiosis (modified Hungate technique) were examined during growth and sporulation by employing Nomarski interference-contrast and Zernike phase-contrast optics to delineate the sequence of morphological changes leading to the formation of free, mature spores. A 0.5% l-arabinose, liquid, complex medium was used to obtain a yield of 30 to 40% free, refractile spores (ca. 10(8)/ml) by 48 hr of incubation. The mean doubling time for the glucose culture (vegetative cells) was found to be 80 min, and that for the l-arabinose culture (sporulating cells), 498 min. By 8 hr of incubation, beginning spore formation became evident in the arabinose culture by the development of a distinct arrowhead-shaped terminal swelling. By 32 hr of incubation or shortly thereafter, Nomarski optics showed the mature spore to be uniformly spherical, whereas the enlarged terminal swelling containing it was not. The use of phase-contrast and interference-contrast optics permitted the characterization of the distinctive morphological changes occurring during sporulation of C. thermosaccharolyticum.